How do different navigation systems affect emergency response time? A prospective simulation study - Daniela Ohlendorf; Fabian Holzgreve; Anke van Mark; Tim Hallstein; David A. Groneberg (BMJ Open)
Objective There has not been a theoretical test run in Germany that compares different navigation systems with an industry solution (MapTrip112). The aim of this study was to compare navigation systems to elucidate whether the emergency response time (ERT) was reduced and, consequently, whether the adherence to the travel time improved.Design Prospective, simulation study, cross-sectional study.Setting Offices of the Institute of Occupational Medicine, Social Medicine and Environmental Medicine, Goethe University Frankfurt (60 590 Frankfurt am Main, Germany). The situation-adaptable industry navigation solution MapTrip112 was tested in its ‘Lights and Siren(s) (L&S)’ mode in comparison to the TomTom and Google Maps navigation systems. MapTrip112 was set to calculate a route that takes special emergency rights of way into account.Outcome measures All three navigation systems simultaneously calculated the distances and durations of fictitious routes. Three scenarios were tested: the University Hospital Frankfurt (60 596 Frankfurt am Main, Germany) and the Central Fire Station 1 (60435 Frankfurt am Main, Germany) served as the starting points for the urban routes, while the Odenwald Health Centre (64 711 Erbach, Germany) served as the starting point for rural routes. The routes’ endpoints were arbitrarily chosen locations inside the customary operational radius. The routes were selected for short and long distances as well as for different periods, including weekdays, weekends and evening rush hour (4–7 pm), in the German cities of Frankfurt am Main and Odenwaldkreis (Southern Hesse).Results The time and distance were calculated for a total of 4650 trips. When comparing travel times and distances between rural and urban areas as well as between weekdays and weekends, statistically significant results were obtained (p<0.001). With time advantages ranging from 23.5 s to 300.5 s (4.75% to 50% of the travel time) on weekdays and weekends, MapTrip112 consistently outperformed both TomTom and Google Maps. For city missions, MapTrip112 achieved time gains of up to 50% over its competitors, with significant advantages during the rush hours and around specific locations such as the University Hospital Frankfurt and Fire Station 1.Conclusion MapTrip112 always achieved the fastest routes although these were not always accompanied by a shortened distance. These findings underscore MapTrip112’s superiority in providing efficient routing solutions across various scenarios. For this reason, the use of this software should be considered in practice and investigated in real-world conditions in further studies.